Pengolahan Ampas Kelapa Dengan Mikroba Lokal Sebagai Bahan Pakan Ternak Unggas Alternatif di Sumatera Barat - Sari Gando Hidayati (Jurnal Embrio, 2011)
This study aims to observe the effect of coconut dregs fermented with local microorganism inoculums of metabolizable energy, nitrogen retention, protein digestibility, intake, weight gain, feed conversion and carcass yield of broiler ration and Income Over Feed and Chick Cost (IOFC). Feeding trials conducted at the Training Center Agriculture UPTD Padang Bandar Buat. While the proximate analysis at the Laboratory of Non-Ruminant Nutrition Laboratory and the Laboratory of Food Technology and Faculty of Animal Husbandry Unand. When the research conducted on April 20, until 5 November 2010. Results obtained adding 15% coconut dregs fermentation in broiler chicken rations can increase metabolic energy, nitrogen retention and protein digestibility. Granting up to 20% coconut dregs provides no significant effect on feed consumption and feed conversion, but the real influence with weight gain and carcass yield of broiler chickens. The conclusion from this study of coconut dregs and 20% of the economically still provide benefits compared to no provision of coconut dregs fermentation, although significantly affect weight gain of broiler chickens